2003
DOI: 10.1038/sj.npp.1300298
|View full text |Cite
|
Sign up to set email alerts
|

The Somatostatin Analogue Octreotide Impairs Sleep and Decreases EEG Sigma Power in Young Male Subjects

Abstract: The long-acting somatostatin (SRIF) analogue octreotide decreased nonrapid eye movement sleep (NREMS) in the rat. This effect is opposite to the promotion of sleep after growth hormone (GH)-releasing hormone (GHRH) in various species including humans. Therefore, it appears likely that GHRH and SRIF, besides their opposite action on pituitary GH release, interact reciprocally in sleep regulation. In previous studies, SRIF impaired sleep in elderly subjects, although sleep in young men remained unchanged. We hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 41 publications
2
22
1
Order By: Relevance
“…There is evidence that central somatostatin is involved in several processes, such as sleep architecture (Beranek et al 1997;Danguir 1986;Frieboes et al 1997;Hajdu et al 2003;Obal et al 2003;Steiger et al 1992;Toppila et al 2000;Ziegenbein et al 2004), epileptiform activity (Binaschi et al 2003;Buckmaster et al 2002;Mazarati and Telegdy 1992;Moneta et al 2002;Tallent and Qiu 2008;Tallent and Siggins 1999;Vezzani and Hoyer 1999), memory formation and retention (Dournaud et al 1996;Dutar et al 2002;Dyer and Cain 2007;Gastambide et al 2009;Justino et al 1997;Kluge et al 2008;Lamirault et al 2001;Low et al 1998;Matsuoka et al 1994Matsuoka et al , 1995Nilsson et al 1993;Tashev and Belcheva 2008;Tokita et al 2005;Zeyda et al 2001), locomotor activity (Hathway et al 2004;Izquierdo-Claros et al 2001;Marazioti et al 2005Marazioti et al , 2006Marazioti et al , 2008Raynor et al 1993;Santis et al 2009;Tashev et al 2001Tashev et al , 2004, and nociception (Betoin et al 1994;Carlton et al 2001;…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that central somatostatin is involved in several processes, such as sleep architecture (Beranek et al 1997;Danguir 1986;Frieboes et al 1997;Hajdu et al 2003;Obal et al 2003;Steiger et al 1992;Toppila et al 2000;Ziegenbein et al 2004), epileptiform activity (Binaschi et al 2003;Buckmaster et al 2002;Mazarati and Telegdy 1992;Moneta et al 2002;Tallent and Qiu 2008;Tallent and Siggins 1999;Vezzani and Hoyer 1999), memory formation and retention (Dournaud et al 1996;Dutar et al 2002;Dyer and Cain 2007;Gastambide et al 2009;Justino et al 1997;Kluge et al 2008;Lamirault et al 2001;Low et al 1998;Matsuoka et al 1994Matsuoka et al , 1995Nilsson et al 1993;Tashev and Belcheva 2008;Tokita et al 2005;Zeyda et al 2001), locomotor activity (Hathway et al 2004;Izquierdo-Claros et al 2001;Marazioti et al 2005Marazioti et al , 2006Marazioti et al , 2008Raynor et al 1993;Santis et al 2009;Tashev et al 2001Tashev et al , 2004, and nociception (Betoin et al 1994;Carlton et al 2001;…”
Section: Introductionmentioning
confidence: 99%
“…In rats, the long-acting somatostatin analog octreotide suppressed NREMS after repeated injections [13]. Moreover, octreotide reduced stage 4 NREMS and REMS during the first half of the night and increased intermittent wakefulness during the second half of the night in young healthy adults [15]. We could not identify polysomnographic studies of the effects of the depot preparations of octreotide or lanreotide on sleep parameters, which are interesting in the light of our results.…”
Section: Discussionmentioning
confidence: 65%
“…In rats, repeated injections of octreotide caused decreases in non-rapid eye movement sleep (NREMS) time and NREMS intensity [13]. In healthy young male subjects octreotide decreased stage 4 NREMS and REMS during the first half of the night [15]. Based on these observations, it is possible that somatostatin treatment in patients with acromegaly may also adversely affect sleep.…”
Section: Introductionmentioning
confidence: 99%
“…Animal and clinical studies have shown that all the components of the somatotropic system are involved in the physiology of sleep regulation: growth hormone-releasing hormone (GHRH) [1,2], somatostatin [3], growth hormone (GH) [4,5,6,7], insulin-like growth factor-I (IGF-I) [8], and the natural GH secretagogue ghrelin [9]. …”
Section: Introductionmentioning
confidence: 99%